2018
DOI: 10.3390/nu10030287
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Processing and Seasonality on the Iodine and Selenium Concentration of Cow’s Milk Produced in Northern Ireland (NI): Implications for Population Dietary Intake

Abstract: Cow’s milk is the most important dietary source of iodine in the UK and Ireland, and also contributes to dietary selenium intakes. The aim of this study was to investigate the effect of season, milk fat class (whole; semi-skimmed; skimmed) and pasteurisation on iodine and selenium concentrations in Northern Ireland (NI) milk, and to estimate the contribution of this milk to consumer iodine and selenium intakes. Milk samples (unpasteurised, whole, semi-skimmed and skimmed) were collected weekly from two large N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
(59 reference statements)
3
14
0
5
Order By: Relevance
“…Just as we found no significant difference in iodine content among retail milk with differing fat content, similar results were obtained in other studies [50][51][52]. However, one study found significantly higher iodine levels in skim than in whole or in semi skimmed [53], although the difference was inconsequential in terms of nutritional impact.…”
Section: Other Reports On Iodine In Milksupporting
confidence: 91%
“…Just as we found no significant difference in iodine content among retail milk with differing fat content, similar results were obtained in other studies [50][51][52]. However, one study found significantly higher iodine levels in skim than in whole or in semi skimmed [53], although the difference was inconsequential in terms of nutritional impact.…”
Section: Other Reports On Iodine In Milksupporting
confidence: 91%
“…The iodine concentration in milk is directly proportional to the iodine levels in feedstuffs. Moreover, the season of milk production and fat content of milk can significantly affect its rate [ 35 ]. Manca et al [ 36 ] found that iodine supplementation did not influence the goat milk fatty acid profile, except for some short-chain fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…This is possibly due to concerns that iodisation may undercut population-level efforts to reduce salt intakes and, consequently, hypertension (2). Neither the UK nor Ireland has ever had a salt iodisation policy, with dietary iodine relying heavily on adventitious intakes, particularly from dairy produce where presence of iodine in cleaning solutions or in animal feed has historically led to iodine entering milk and dairy produce (2,3). Without any iodised salt policy, a number of studies have investigated iodine intake and status in UK and Irish populations, suggesting some concern (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%